New data on mitogenomes of Thienemanniella Kieffer, 1911 (Diptera: Chironomidae, Orthocladiinae) - Qi, Yan; Bu, Wen‐Jun; Zheng, Chen‐Guang; Lin, Xiao‐Long; Jiao, Ke‐Long (Archives of insect biochemistry and physiology, 2023)
The mitochondrial genome (mitogenome) has been widely used as a powerful marker in phylogenetic and evolutionary studies of various Dipteran groups. However, only a few mitogenomes from the Thienemanniella genus have been reported till now. Furthermore, there is still indeterminacy in the phylogenetic relationships of the genus Thienemanniella . In this study, mitogenomes of five Thienemanniella species were sequenced and analyzed newly. Combined with the published mitogenome of Thienemanniella nipponica , the obtained results showed that mitogenomes of Thienemanniella were conserved in structure, and all genes were observed to be arranged in the same gene order as the ancestral mitogenome. Nucleotide composition varied significantly among different genes, and the control region displayed the highest A + T content. All protein coding genes are subjected to purification selection, and the fastest evolving gene is ATP8 . Maximum likelihood and Bayesian inference analyses showed the phylogeny of Thienemanniella which was supported in five topologies. Our present study provides valuable insight into the phylogenetic relationships of Thienemanniella species. We sequenced and analyzed the mitogenomes of five Thienemanniella species to reveal mitogenomic organization, base composition, and evolutionary rates of this genus. The phylogenetic trees by BI and ML explored the interspecific relationship within Thienemanniella .